2018
DOI: 10.21307/stattrans-2018-015
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Exponential Type Estimator of Population Mean in the Presence of Non-Response

Abstract: In this article, we propose a class of generalized exponential type estimators to estimate the finite population mean by using two auxiliary variables under non-response in simple random sampling. The proposed estimator under non-response in different situations has been studied and gives minimum mean square error as compared to all other considered estimators. Usual exponential ratio type estimator, exponential product type estimator and many more estimators are also identified from the proposed estimator. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Sharma and Pal (2018) proposed improved ratio type estimator for the estimation of population mean in presence of random non-response. Muneer et al (2018) suggested a generalized exponential ratio type estimator of population mean in the presence of non-response Toutenberg and Srivastava (1998); Toutenberg and Srivastava (2003) studied the problem of estimation of ratio of two population means and the population mean respectively in survey sampling when some observations are missing on study and auxiliary variables. Sinha (2007, 2009) also suggested enhanced estimation of the ratio of the two population means using multi auxiliary characteristics in the presence of non-response.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and Pal (2018) proposed improved ratio type estimator for the estimation of population mean in presence of random non-response. Muneer et al (2018) suggested a generalized exponential ratio type estimator of population mean in the presence of non-response Toutenberg and Srivastava (1998); Toutenberg and Srivastava (2003) studied the problem of estimation of ratio of two population means and the population mean respectively in survey sampling when some observations are missing on study and auxiliary variables. Sinha (2007, 2009) also suggested enhanced estimation of the ratio of the two population means using multi auxiliary characteristics in the presence of non-response.…”
Section: Introductionmentioning
confidence: 99%
“…T ) under call-back has minimum MSEs and higher PREs than most of the estimators under study with the exception of Salim and Onyango [29] so t , Muneer et al [28] estimators  …”
Section:    mentioning
confidence: 87%
“…Munneer et al [28] proposed exponential type estimators of population mean in the presence of non-response as in ( 5) -( 14)…”
Section: mentioning
confidence: 99%
“…In the context of nonrespond, [11] introduced an elevated ratio estimator for estimating Ȳ. For the issue of non-respond, [12] proposed an exponential type generalized estimator of Ȳ. While some observations on Y and X are missing, [13,14] investigated the challenge of estimating the ratio of two Ȳ in survey sampling.…”
Section: Introductionmentioning
confidence: 99%